ICTs as Innovative Tools in the University Teaching: The Case of the Escuela de Literatura y Ciencias del Lenguaje at the Universidad Nacional - Pizarro Chacón, Ginneth (2014)
The current university systems demands that teachers adapt and implement their teaching processes to encourage the proper use of technology resources. These technological tools help teachers and learners make effective group work, promote social activities, exchange ideas, have a quick access to information, encourage student-teacher interactions in real time and get access to forums, chats, Web 2.0, among others. This new vision helps teachers interact with their students, plan effective lessons and design learning environments with the use of the communication tools currently available. The innovative combination of technology and the use of traditional and communicative teaching techniques of a particular subject matter will encourage teachers to change their traditional ways of teaching using just lectures, practical classes, and seminars, among others. Through this new perspective, the teacher becomes a facilitator and a guide, and the student will assume a more active role in their learning process. The aim of this paper is to analyze how the teachers at Escuela de Literatura y Ciencias del Lenguage at the Universidad Nacional integrate ICTs into their teaching processes. A questionnaire will be used to get teachers’ experiences in the use or the lack of usage of the ICTs Finally, some updated trainings on the use of technology resources will be recommended to all those teachers who do not use them in the classroom activities, and the exchange of ideas by those who use them will be taken into account to promote class planning and interactive activities as part of their teaching strategies.